2018
DOI: 10.1016/j.conctc.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The rationale, design, and methods of a randomized, controlled trial to evaluate the efficacy of single-dose dexamethasone in reducing post-embolization syndrome in patients undergoing uterine artery embolization

Abstract: BackgroundUterine artery embolization (UAE) is a minimally invasive technique well established for treating symptomatic uterine fibroids. However, the post-procedure recovery for UAE involves a notable inflammatory process in response to ischemia known as post-embolization syndrome (PES). PES encompasses transient leukocytosis, low-grade fever, and can result in readmission of up to 10% of patients. In surgical settings, multiple studies have demonstrated the efficacy of glucocorticoids in reducing inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…The addition of corticosteroids to SHPB increases the duration of analgesia after UAE 3,13,23,24 . Stewart JK et al 13 showed that adding triamcinolone to SHPB resulted in prolonged analgesia after UAE in 16 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of corticosteroids to SHPB increases the duration of analgesia after UAE 3,13,23,24 . Stewart JK et al 13 showed that adding triamcinolone to SHPB resulted in prolonged analgesia after UAE in 16 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Visual analog scale (VAS): the initial VAS, reported immediately at the end of UAE, and the final VAS, between twelve and fourteen hours after SHPB and before discharge, were obtained. The scale was reported as mild (0-2), moderate (3)(4)(5)(6)(7), or severe (8-10) pain.…”
Section: Study Population and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylprednisolone produces significant anti-inflammatory effects by inhibiting the NF-kB pathway and upregulating anti-inflammatory mediators ( 13 ). Glucocorticoids can inhibit the vascular and cellular phases of inflammation and release of BKs, and reduce the inflammatory response secondary to ischemic changes ( 26 ). However, the use of glucocorticoids can cause elevation of white blood cell levels, and the greater the dosage, the more obvious the increase in leukocyte levels the following day ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that glucocorticoids, particularly dexamethasone, are effective at reducing postoperative inflammation and pain in procedural settings. 25,26 Kim et al used 0.2 μg/kg/h dosing 30 minutes prior to UAE and 0.6 μg/kg/h 6 hours postprocedure. 27 In that study, the group that received dexamethasone required 28% less of the fentanyl PCA, had lower pain scores, and needed fewer analgesics than the control group.…”
Section: Dexamethasonementioning
confidence: 99%